Sosialisasi dan Menanam Tanaman Obat Keluarga (TOGA) di Desa Tanjung Harapan (STMIK Dharmapala Riau, 2024)
One of the efforts to increase immunity in the midst of the increasing cases of the COVID-19 pandemic is by consuming herbal drinks that can be obtained from the planting of family medicinal plants (TOGA) such as ginger, turmeric, and lemongrass. Consume it by boiling the three ingredients together and then drinking the water. This activity is one form of the Real Work Lecture (KKN) program which aims to increase public knowledge about the benefits of growing family medicinal plants (TOGA). The activities carried out are providing education and training on planting family medicinal plants (TOGA) which can be planted around the yard of the house. This activity was carried out on Thursday, July 13, 2023, at Tanjung Harapan Village with the target of parents and civil in this Tanjung Harapan Village.